A defesa judicial do Estado brasileiro nas varas federais: estudo de caso na Advocacia-Geral da União - AGU - Teixeira, Luiz Fernando Chalita (2000)
There is no information whatsoever of a society in which there are no demands among private people and companies, among individuals and institutions, varying only the tenor and the intensity of the issues. It would be ideal if conflicts could be solved in common aggreement. The selfcomposition, yet, does not often occurr; leaving the remaining issues for a third part, i.e., the State. Up to the English and French Revolutions, political power was exercised by limitless governors and the State did not submit to the law. After those revolutions, rules are agregated to curb Absolutism and organize the State, which starts to acccomplish its duties under the law, i.e., a Law State. As a result, today, the individual can sue the State to make the State perform or not any undesirable action. In this dissertation, one traces back from the very beginning the role of the institutions in charge of defending the State in courts of law. The judicial defense of the Brazilian State in a court of law, since 1608 to the 1988 Constitution, was a role of the Public Ministry, along with other institutional functions, including prosecution. As a consequence of this ambivalence, the results of the State defense came even to be contradictory. The promulgation of the 1988 Federal Constitution adjusted this historical dualism. The 1988 Constituent embodied significant change to the concept and operationalization of a State Advocacy, confering to a new institution , which was called 'Advocacia Geral da União' or 'General Advocacy of the Union' (article 131), the judicial and extrajudicial representation of the Union. The final object of the reflections of this study is centred on the analysis of the activities of the 'General Advocacy of the Union', in its first years of functioning, in other words, from 1993 to 1999